PEMANFAATAN JAMUR TIRAM UNTUK KEBUTUHAN PANGAN SEBAGAI KEARIFAN LOKAL MASYARAKAT PERKOTAAN - Prihatini, Lishapsari; Marleni, Marleni (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2020)
Oyster mushroom cultivation training is an effort to facilitate training participants so they can develop independence and fulfill food needs by providing knowledge and skills. The research objectives: 1) identify the ability of the trainees to utilize the results of the training, 2) obtain an overview of the motivation of the training participants in utilizing the results of the oyster mushroom cultivation training, and 3) analyze the driving factors and inhibiting factors encountered in developing an oyster mushroom cultivation business. The driving factor for oyster mushroom cultivation is the availability of natural potential as a material for making planting media, capital, and demand for oyster mushrooms which is never lacking from the market. The inhibiting factors are land, technology, and support from the government.